Synthetic Studies of Haliclonin A: Construction of the 3-Azabicyclo[3.3.1]nonane Skeleton with a Bridge that Forms the 17-Membered Ring - Orihara, Kensuke; Kawagishi, Fumiki; Yokoshima, Satoshi; Fukuyama, Tohru (Synlett, 2018)
The core structure of haliclonin A, a 3-azabicyclo[3.3.1]nonane with a bridge that forms a 17-membered ring, was constructed. The synthesis features a ring-closing metathesis that constructs the macrocyclic ring, the stereoselective introduction of carbon units via the intramolecular cyclopropanation of a diazoester, the conjugate addition of an organocopper reagent, and the formation of 3-azabicyclo[3.3.1]nonane skeleton via an unexpected 1,5-hydride shift.
Keywords: alkaloids; conjugate addition; heterocycles; hydride shift; macrocycles; marine natural products; ring-closing metathesis